Eco Enzyme Sebagai Alternatif Pengolahan Limbah Lahan Pertanian dan Rumah Tangga Menjadi Pupuk Organik Bagi Petani di Desa Nian - Yosefina M Fallo; Dira A Pramita; Marselina TD Tea (Lembaga Pengembangan Kinerja Dosen, 2024)
Problems related to waste have become a hot issue in the community and have received serious attention from policymakers. One practical way to overcome this problem is to manufacture eco-enzyme products whose raw materials use organic waste. Eco enzyme is a fermented process from organic kitchen waste such as fruit and vegetable pulp, sugar, and water until it becomes the final product in liquid fertilizer. This service aims to describe community social activities to overcome waste problems using the eco enzyme concept. The activities carried out were providing counseling related to how to manage household organic waste into eco-enzyme products, introducing and training the use of composter technology to process household organic waste into eco-enzyme products, and motivating and encouraging people to manage household waste into products of economic value. This study uses several methods such as presentation, discussion, question and answer, training, and evaluation handled by lecturers of the Faculty of Agriculture, Timor University. The study results show that people can apply eco enzyme technology, know how to use it, and produce economic value from organic waste.